A Firm Lower Bound : Characteristics and Impact of Corporate Minimum Taxation - Aslam, Aqib (IMF Working Papers; Working Paper ;, 2021)
This paper examines the role of minimum taxes and attempts to quantify their impact on economic activity. Minimum taxes can be effective at shoring up the corporate tax base and enhancing the perceived equity of the tax system, potentially motivating broader taxpayer compliance. Where political and administrative constraints prevent reforms to the standard corporate income tax, a minimum tax can help mitigate base erosion from excessive tax incentives and avoidance. Using a new panel dataset that catalogues changes in minimum tax regimes over time around the world, firm-level analysis suggests that the introduction or reform of a minimum tax is associated with an increase in the average effective tax rate of just over 1.5 percentage points with respect to turnover and of around 10 percent with respect to operating income. Minimum taxes based on modified corporate income lead to the largest increases in effective tax rates, followed by those based on assets and turnover.